2004
DOI: 10.1007/s11661-004-1016-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of carbide-particle-reinforced titanium aluminide-matrix composites by laser-engineered net shaping

Abstract: TiAl-based titanium aluminide alloys and their composites reinforced with ceramic particles are considered to be important candidate materials for high-temperature structural applications. Laser-engineered net shaping (LENS) is a layered manufacturing process, which involves laser processing fine powders into three-dimensional components directly from a computer-aided design (CAD) model. In this work, the LENS process was employed to fabricate carbide-particle-reinforced titanium aluminide-matrix composites us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The phenomenon of TiC particle melting during exposure to a laser beam has also been noted by another investigator [13] and rationalized by the fact that TiC particles have a much higher capability to absorb laser energy than that of metals. In fact, ceramics absorb energy better than metals only at both ends of the spectrum of wavelength: 0.1 to 10 lm, such as for a CO 2 laser with a wavelength of 10.6 lm, but worse than metals in the case of a Nd:YAG laser, whose wavelength is 1.064 lm.…”
mentioning
confidence: 69%
“…The phenomenon of TiC particle melting during exposure to a laser beam has also been noted by another investigator [13] and rationalized by the fact that TiC particles have a much higher capability to absorb laser energy than that of metals. In fact, ceramics absorb energy better than metals only at both ends of the spectrum of wavelength: 0.1 to 10 lm, such as for a CO 2 laser with a wavelength of 10.6 lm, but worse than metals in the case of a Nd:YAG laser, whose wavelength is 1.064 lm.…”
mentioning
confidence: 69%
“…The hardness reached 2300 HV with a high content of ceramics, which is more than 11x the hardness of pure Ti [14]. Also, Liu et al [47] found that pre-heating the substrate is an effective method for eliminating cracks during the LENS process. Crack-free deposits were obtained with a substrate pre-heated between 450 and 500°C, laser power of 300 W and scan speed less than 762 mm/min.…”
Section: Properties and Samplesmentioning
confidence: 98%
“…The powders (particle size between 45 and 150 μm) were placed in separate feeders and mixed in situ while feeding from the powder feeders to the nozzles. On the other hand, the same authors deposited Ti-48Al-2Cr-2Nb and TiC (20 vol%) powder (particle diameters also between 45 and 150 μm) on the same substrate [47]. In this case, the powders could pre mixed and placed in a single powder feeder since the proportion in this case was not variable.…”
Section: Raw Materials and Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Both types of porosity decrease with increase of traverse speed and power level. Liu and DuPont [5] reported that LENS TM is convenient for metals and alloys: H13, 316 stainless steel, nickel-base superalloys and titanium alloys. A problem in depositing alloys by LENScracks in the deposits.…”
Section: Introductionmentioning
confidence: 99%